Pengaruh Budaya Organisasi, Motivasi Kerja Dan Komitmen Organisasi Terhadap Kinerja Karyawan Pada PT. Adiwraksa Atyanta. - Miftahul Jannah, Ulfa, Drs. Farid Wajdi, MM, Ph.D (2017)
ABSTRAC This study aimed to analyze the influence of organizational culture, motivation and organizational commitment to employee performance at PT. Adiwraksa Atyanta. This research. done by using a sample of 100 people, the data collected by using a questionnaire in the form of a list of questions. Data used using SPSS 16.0 program using validity, reliability test, regression analysis, t test, F test, test the coefficient of determination. The results of hypothesis testing are: organizational culture, work motivation and organizational commitment affect the performance of employees at PT. Adiwraksa Atyanta, F test results can be concluded together that organizational culture, work motivation, and commitment of a significant effect on the performance of employees at PT. Adiwraksa Atyanta, based on results of multiple linear regression analysis showed that organizational culture significantly influence employee performance, motivation significantly influence employee performance and organizational commitment significantly influence employee performance in PT. Adiwraksa Atyanta. Keywords: Organizational Culture, Motivation, Organizational Commitment, Employee Performance.